MEMBANGKITKAN SEMANGAT JIWA MUDA UNTUK MEMBANGUN DEMOKRASI YANG TENTRAM DAN DAMAI - Hani Hanifah Bilqis; Siti Elissa Nursetiaamana; Dea Muhammad Azka Azzuhdi; Zaenul Slam (STKIP Subang, 2026)
The younger generation holds a crucial position in promoting and sustaining democratic life in Indonesia. In the era of globalization and rapid technological advancement, young people face various challenges, including declining national awareness, the spread of misinformation, and reduced civic engagement. These issues have the potential to weaken social cohesion and undermine the development of a peaceful democratic society. This article seeks to explore the significance of fostering youth spirit and civic responsibility in strengthening democracy through the cultivation of nationalism, tolerance, political participation, and adherence to Pancasila values. The study employs a qualitative approach using library research methods by examining relevant books, journals, and other academic sources. The findings reveal that young people play a vital role as agents of change, democratic watchdogs, and active participants in political and social processes. Their involvement in elections, public discourse, and the constructive use of digital media can contribute positively to democratic development. Furthermore, the internalization of nationalism, tolerance, and Pancasila values serves as an essential foundation for maintaining unity and social harmony in Indonesia’s diverse society. Character education and digital literacy are also important instruments for developing a generation that is critical, responsible, and capable of responding wisely to the challenges of the digital age. Therefore, strengthening the spirit and awareness of young people is essential for fostering a democratic, peaceful, and sustainable future for Indonesia.